The Incidence of Complications is Low Following Foot and Ankle Surgery for Which Peripheral Nerve Blocks Are Used for Postoperative Pain Management. Issue 2 (July 2018) - Kahn, Richard L.; Ellis, Scott J.; Cheng, Jennifer; Curren, Jodie; Fields, Kara G.; Roberts, Matthew M.; YaDeau, Jacques T.
Background: The incidence of neurologic complications from foot and ankle surgery utilizing regional anesthesia is not well established. Questions/Purposes: The purpose of this study was to prospectively determine the incidence of neurologic and peripheral nerve block (PNB) site complications on a busy foot and ankle service that utilizes ankle blocks (ABs) and popliteal blocks (POPs). Patients and Methods: This prospective observational study included patients undergoing foot and ankle surgery with ABs or POPs. Block choice was determined by surgeon's preference. Patients were assessed for complications during postoperative visits at 2, 6, and 12 weeks. The relation of each complication to the block was scored by a surgeon and anesthesiologist. Results: From October 2012 to October 2014, 2516 patients underwent 2704 surgeries. There were 195 complications (7.2%) considered neurologic or at the PNB site. The incidence of serious complications was 0.7%. A higher complication rate was reported for POPs (8.8%) than for ABs (2.5%). However, when analysis was limited to forefoot surgery, this difference was not significant. Dexamethasone use was associated with increased complications for POPs. Only 5 of the 195 total complications, and 2 of 20 serious complications, were deemed to have been likely caused by the block by both the surgeon and anesthesiologist reviewer. Conclusions: The incidences of neurologic or block-related complications and serious complications were 7.2 and 0.7%, respectively, most without a clear surgical vs. nerve block etiology. The higher complication rate for POPs using perineural dexamethasone should be interpreted cautiously in light of the lack of randomization and likely confounders.